2006
DOI: 10.1002/anie.200600353
|View full text |Cite
|
Sign up to set email alerts
|

A Surface‐Bound DNA Switch Driven by a Chemical Oscillator

Abstract: The fabrication of autonomously moving molecular structures is one of the central challenges in the field of DNA nanodevices.[1] Some of the concepts introduced recently to achieve this goal rely on the sequence-dependent catalytic action of DNA-modifying enzymes such as restriction endonucleases or nicking enzymes [2] while others use the catalytic power of DNA itself by incorporating DNA enzyme sequences into DNA devices.[3] Both approaches have also been used to realize autonomous molecular computers.[4] A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 25 publications
(14 reference statements)
0
77
0
3
Order By: Relevance
“…The reported examples are mostly operated by adding chemicals or fuel DNA molecules that are easily realized in bulk systems, but not under nanoscale. In 2005, Leidl et al [32] reported autonomous switching of DNA motor and surface optical signals for several times using an improved pH oscillator system. In 2007, Liu et al [33] reported a light-driven method, enabling non-contact driving of the i-motif DNA motor for the first time.…”
Section: Smart Surfaces Based On Dnamentioning
confidence: 99%
“…The reported examples are mostly operated by adding chemicals or fuel DNA molecules that are easily realized in bulk systems, but not under nanoscale. In 2005, Leidl et al [32] reported autonomous switching of DNA motor and surface optical signals for several times using an improved pH oscillator system. In 2007, Liu et al [33] reported a light-driven method, enabling non-contact driving of the i-motif DNA motor for the first time.…”
Section: Smart Surfaces Based On Dnamentioning
confidence: 99%
“…Der i-Motiv-Schalter reagiert auf pH-Oszillationen sogar dann mit großer Reversibilität, wenn er auf einer Oberfläche immobilisiert wird. [124] Diese beiden Studien waren wichtige Vorstufen für die Entwicklung eines i-Motiv-DNA-Schalters, der reversibel auf den pH-Wert der Umgebung innerhalb einer lebenden Zelle reagiert, wenn er auf einer biologischen Oberfläche -nämlich an der Innenseite einer endosomalen Membranangelagert ist (siehe Abschnitt 7). [121] Verschiedene i-Motiv-Schalter überführen die chemische ¾nderung des pH-Werts in andere messbare ¾nderungen der Eigenschaften der betrachteten Anordnung.…”
Section: I-motiv-schalterunclassified
“…In more nanotechnology-oriented work along these lines, it has been previously shown that reaction-diffusion systems can be used to produce microand even nanoscale patterns (Grzybowski et al, 2005). In the context of DNA nanotechnology it was demonstrated that chemical oscillators can drive DNA conformational changes (Liedl et al, 2006).…”
Section: Artificial Developmentmentioning
confidence: 99%